Blood pressure, antihypertensive drug treatment and the risks of stroke and of coronary heart disease. - Collins, R; MacMahon, S (1994)
Most evidence about the effects of blood pressure on the risks of cardiovascular disease derives from two principal sources: prospective non-randomised observational studies of the associations between blood pressure and the incidence of stroke and of coronary heart disease, and randomised trials of antihypertensive drug therapy. The focus of the first part of this chapter concerns the evidence from observational studies, which--despite the possibility of confounding by other risk factors--may be more relevant to the eventual effects of prolonged blood pressure differences on stroke and coronary heart disease risk. The focus of the second part concerns the evidence from randomised trials of antihypertensive drug treatment, which are more relevant to assessing how rapidly, and to what extent, the epidemiologically expected reductions in stroke or in coronary heart disease are produced by suddenly lowering blood pressure in middle and old age.